Health education in the press. Analysis of Basque and Navarrese newspapers (Communication & Society, 2014)
This article aims to describe quantitatively the media coverage of health issues published in the Basque newspapers El Correo, Noticias de Gipuzkoa, Noticias de Álava and Berria and in the Navarrese Diario de Navarra during the decade 2001-2010, to determine quantitatively which of those health related articles have an educational approach and, at the same time, to gather different qualified points of view on the press’s role in health education. This study was done with a content analysis and in-depth interviews with five journalists and eight health professionals. The study concludes that it is necessary for the newspapers to work in order to improve health education they usually publish.